Obispos y mártires palestinos: el caso de Gaza (s. IV) - Aja Sánchez, José Ramón (Gerión. Revista de Historia Antigua, 2001)
One of the cities less representative of the Christianity in Palestine —and in addition of all the Oriens Diocese— was Gaza, among other reasons because pagan cults lasted there —long and strongly but with little social and political resistance—. Pagans’ sanctuaries were still open at the beginning of 5th century AD and most of its population perceived themselves as pagans well in the second half of the same century. Gaza’s Bishops had to accept and deal with this circumstance. This paper tries to emphasize the peculiarities of this Polis —Gaza— and its «chora, » in this matter, going deep in the role played by its Bishops and its Holy Native Martyrs in the context of the Palestinian Christianity expansion during the 4th century AD and the beginnings of 5th.